2023
DOI: 10.3390/ani13172759
|View full text |Cite
|
Sign up to set email alerts
|

Fish and Black Soldier Fly Meals as Partial Replacements for Soybean Meal Can Affect Sustainability of Productive Performance, Blood Constituents, Gut Microbiota, and Nutrient Excretion of Broiler Chickens

Youssef A. Attia,
Fulvia Bovera,
Khalid A. Asiry
et al.

Abstract: One hundred and twenty, one-day-old male broiler chicks were used to investigate the effects of supplementation with different dietary protein sources on their performance and immune systems. Chicks were randomly divided into four equal experimental groups (six replicates, each of five chicks). The first group served as a control and was fed a standard corn–soybean meal diet. The second, third, and fourth groups were fed diets in which the soybean meal (SBM) was partly replaced by fish meal (FM), black soldier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…An increase in the blood ALT and AST levels due to the inclusion of BSF larvae meal was also reported in [47,60]. In contrast to these findings, Dabbou et al [49] and Attia et al [61] reported that a soybean-based diet partially substituted with BSF larvae did not affect the serum ALT, AST, triglycerides, or uric acid levels. ALT and AST are specific indicators of liver health.…”
Section: Blood Parameters and Organ Weightsmentioning
confidence: 84%
“…An increase in the blood ALT and AST levels due to the inclusion of BSF larvae meal was also reported in [47,60]. In contrast to these findings, Dabbou et al [49] and Attia et al [61] reported that a soybean-based diet partially substituted with BSF larvae did not affect the serum ALT, AST, triglycerides, or uric acid levels. ALT and AST are specific indicators of liver health.…”
Section: Blood Parameters and Organ Weightsmentioning
confidence: 84%
“…A comprehensive analysis of past research reveals varying outcomes regarding the impact of BSFL on broiler chicken growth as shown in Table 2. In conducting a comprehensive literature review, particularly studies by Dabbou et al [21], Facey et al [112], Fruci et al [113], Mat et al [114], Nampijja et al [115], Bellezza Oddon et al [116], Ipema et al [117], Seyedalmoosavi et al [118], Attia et al [119], Heita et al [120], and Murawska et al [121], a detailed understanding emerges regarding the impact of both defatted (DF) and full-fat (FF) BSFL on the growth performance of different broiler chicken breeds. The earlier set of studies, focusing on DF BSFL, provides insights into how varying inclusion levels of this alternative protein source affect broiler chickens.…”
Section: Growth Performancementioning
confidence: 99%
“…Some levels resulted in a decrease in FI and an improvement in BWG, whereas others, particularly at higher inclusion rates, suggested potential negative impacts. Furthermore, in recent studies by Attia et al [119] and Heita et al [120], the effects of 5% and 10% FF BSFL inclusion in the diets of Arbor Acres and Ross-308 broiler chickens were examined over 42 days. Attia et al [119] reported that a 5% inclusion level of FF BSFL in Arbor Acres chickens did not significantly alter FI, FCR, or BWG.…”
Section: Growth Performancementioning
confidence: 99%
See 2 more Smart Citations